Career awareness in the study of Malay language program - Jusoh, Zuraini; Said, Rozita Radhiah; Mohd Kiram, Norazlina (Universitas Negeri Makassar- Faculty of Languages and Literature, 2021)
Awareness of the career to be pursued can be present as early as childhood and can vary according to knowledge and interest. Most of today's children are more focused on achieving excellence in education, but still vague in the career that will be pursued. This situation persisted when they continued their studies at higher education and they realized that the choice of field of study was not in line with their ambitions. Usually, these children choose a field based on their results rather than settling for the required degree for the field of interest. Therefore, this study was conducted to determine the extent of students’ understanding of the scope and career prospects in Malay language. Students were distributed with a set of questionnaires containing 54 items using ordinal scales of semantic difference types. The findings of the study showed that 34(56.7%) of the students studied chose this field of study as the main choice. Students also showed a high level of knowledge about careers in the Malay language which they studied (M=3.92; SD=0.57). Students have also listed a total of 14 careers in the field of Malay language they are familiar with.